Agglomeration economies in Italy: Impact on heterogeneous firms' survival - Anna Maria Ferragina; Fernanda Mazzotta (European Regional Science Association (ERSA), 2014)
The focus of our contribution is to shed light on the importance of firm agglomerations and FDI as drivers of firm survival in Italy. We focus upon different types of agglomeration economies related to the geographical context checking how these economies impact differently on heterogeneous firms survival and whether effects are robust to different estimators (Probit, Cox hazard models, Probit Heckman) and to different assumptions about inter-and intra-regional spillovers. The novelty our paper with respect to previous studies is twofold. First of all, we focus both on external economies and on firm internationalization, two crucial determinants of firm productivity and competitiveness and ultimately of firm survival. Hence, we consider the intertwined role of firm global activities with respect to the local drivers of firm dynamics by comparing foreign investors in Italy and Italian firms' investing abroad to domestic firms to catch a crucial source of heterogeneity of firm behavior with respect to external economies (correcting for the endogeneity of the FDI variables and for sample selection). Secondly, we use a very large dataset at firm level which takes into account several different dimensions at firm, industry and province level (previous studies are mostly at sectoral or at province/regional level) for more than 500,000 observations concerning Italian manufacturing corporate firms disaggregated by sector and by 103 provinces over a long span of time (2002-2010) which allows to also catch the effect of the crisis. With respect to agglomeration economies the paper analyses whether and how firms' exit choices are influenced by five different agglomeration indicators related to the geographical context: 1) External economies arising from localization economies due to the spatial concentration of firms in the same industry (GLAESER et al., 1992) and to 2) local production systems (Industrial districts); 3) External economies available to all local firms irrespective of sector and arising from urban size and density (urbanization economies); 4) External economies available to all local firms stemming from specialisation of firms in different varieties which may favour intra- and inter industry knowledge spillovers via Jacobs externalities (JACOBS, 1969); 5) diversification due to unrelated variety to capture the portfolio effect arising from the spatial concentration of firms belonging to different and non-complementary industries which may protect the region from sector-specific shocks (FRENKEN et al., 2007). We check whether the relevance of these agglomeration economies differ substantially between Italian firms and firm which invest in active or passive FDI. We get evidence on three issues: 1) Benefits from geographically and industry bounded specialisation for survival; 2) Industrial districts economies impact on firm survival 3) Diversification economies relevance.
Keywords: C41; F21; F23; L25; 330